Psychological-motivational component of schematic representation of Italian language grammar [Психолого-мотивационная составляющая схематического предъявления грамматики итальянского языка] (in Russian) - Ivanchenko, Andreyanna; Иванченко, Андреянна Алексеевна; Іванченко, Андреянна Олексіївна (Харьков : ХНУ, 2006)
It was shown an efficiency of the aim creation in the course of the Russian as foreign or English language studding by means of the grammar’s schematization and of the rejection of aspectization in teaching. It was proposed a novel approach to teaching/learning of other language reality that permit to take in consideration a motivation, emotional and creative activity components. Показана эффективность целеформирования при усвоении итальянского (и русского как иностранного) языка путем использования схематизации грамматики и отказа от аспектного обучения. Предложен новый подход к процессу преподавания/усвоения новой языковой реалии, позволяющий учесть мотивационно-эмоциональный и креативный компоненты деятельности. It was shown an efficiency of the aim creation in the course of the Russian as foreign or English language studding by means of the grammar’s schematization and of the rejection of aspectization in teaching. It was proposed a novel approach to teaching/learning of other language reality that permit to take in consideration a motivation, emotional and creative activity components.
Keywords: мотивация и синергия; Синергетический Культурологично-Экзистенциальный Системный (СКЭС) подход; целеформирование; эмоции; лингвопреподавания; психология запоминания; motivation and synergy; SCES approach; aim forming; emotions; language teaching; memory psychology